(untitled) (Altre Modernità, 2015)
Moving from Adorno’s statement about the enigmatic nature of modern aesthetics, this paper aims to analyse the forms the enigma takes in the works of the Uruguayan and Argentinian poets Sara de Ibáñez and Alejandra Pizarnik. The essay will consider the figures and the shapes of the enigma as they appear in both poetries. Proper of the revelation of the enigma through its profanation by the poetic language is, in fact, the never-ending and mutual reflection of two different states of the being. Through Martin Heidegger and Giorgio Agamben’s studies on language and negativity, the way in which the enigmatic word appears continuously in its constitutive suspension between infancy and adulthood, absence of time and history, language and silence, the Self and the Other will be revealed. Through the resulting dichotomy of matter and form, emerging from a passage of Agostino’s De natura boni, it will be possible, in conclusion, to recognise in the silent form of the enigma the embryonic proposal of a poetical ethics of writing.